(untitled) (Conferencea, 2023)
This article deals with stylistic devices as a cultural model of language.A stylistic device can indeed serve as a cultural model, as it reflects the values and beliefs of a particular culture. Stylistic devices such as metaphors, similies and allusions often draw on cultural references and symbols to create meaning and convey messages. Stylistic devices are techniques used by writes to create a certain effect or emphasize a particular aspect of their novels or stories. These devices can be divided into different categories, including: figurative language, repetition, imagery, irony, allusion.